Morphological and phylogenetic study of Acanthosquilla Manning, 1963 (Stomatopoda: Nannosquillidae) mantis shrimps, with description of two new species from the Ryukyu Islands, Japan - Nakajima, Hiroki; Reimer, James Davis; Naruse, Tohru (Zootaxa, 2023)
Three species of nannosquillid mantis shrimps, including two new species, Acanthosquilla ryukyuensis n. sp. and Acanthosquilla shoheii n. sp., are described based on specimens collected from the Ryukyu Islands, Japan. The two new species resemble A. derijardi Manning, 1970, but can be distinguished from A. derijardi by the following features: 1) rostral plate anterolateral corner forms almost a right angle; 2) the distal tip of the antennular somite dorsal process reaches or slightly falls short of proximal half of rostral plate; and 3) eighth thoracic somite (= TS8) posterior margin is black medially. Furthermore, A. ryukyuensis n. sp. and A. shoheii n. sp. are easy to identify by the bifurcated lateral tooth of the telson, and by the posterodorsal pattern of the telson, respectively. In this study, molecular analyses based on partial sequences of mitochondrial 12S and 16S ribosomal DNA, cytochrome oxidase subunit I (COI), and the partial nuclear gene of 28S ribosomal DNA recovers these three species of Acanthosquilla and A. multifasciata (Wood-Mason, 1895) (the type species of the genus) in a single clade. The resulting trees also suggest the polyphyly of Nannosquillidae but with low nodal support. Detailed examinations of the morphological and color features and DNA barcoding results allowed us to delineate intraspecific variations and interspecific differences. The number and shape of setae under the dorsal spine of raptorial claw carpus was found to be useful in distinguishing A. shoheii n. sp. from A. derijardi and A. ryukyuensis n. sp., while combinations of the coloration of the rostral plate, posterior margin of TS8 and posterodorsal surface of telson are useful to distinguish the three species.